Modal behaviour of spur gear pairs for a low speed transmission application - a comparative study between symmetric and asymmetric gears. (11th January 2023) - Gupta, Krishanu; Chatterjee, Sushovan
Modal analyses on the types of involute profile spur gear is investigated in this work using the FEM analysis platform considering the no-load condition. The gear pairs' resonance frequency behaviours were mapped against the first six mode shapes. A comparison study has also been carried out for the involved types of gear pairs, making it prominent, between symmetric and asymmetric gear pairs. From this analysis, it was noticed that the asymmetric gear pair bears a high range of resonating frequencies in comparison to other symmetric involute gear teeth pairs. Attempts have been made to examine a specific range of higher values of frequencies for asymmetric gear pair than any other asymmetric pairs at different modes by modal analysis.